Climate change will render size‐selective harvest of cold‐water fish species unsustainable in Mediterranean freshwaters. Issue 3 (13th December 2020) - Ayllón, Daniel; Nicola, Graciela G.; Elvira, Benigno; Almodóvar, Ana
Abstract: Climate change is impacting the composition and functioning of virtually every ecosystem on Earth, and disrupting the productivity of exploited ones. Species are rapidly adjusting to their changing environments through evolutionary and/or plastic phenotypic changes in behavioural, physiological, phenological and life‐history traits. Size‐selective harvest produces severe demographic impacts on exploited populations and induces individual phenotypic changes in many of the same fitness‐related traits as climate change and thus can impair local adaptation and acclimation. We addressed in the context of inland recreational fisheries two interrelated questions: (1) Will fisheries‐induced phenotypic changes operate at different rates and direction than those induced by climate change, and thus hinder local adaptation and acclimation, threatening population persistence?; (2) which harvest regulations most likely lead to overexploitation of populations under the new environmental conditions? We used an eco‐genetic individual‐based model to simulate the consequences of size‐selective fishing for a cold‐water fish species brown trout Salmo trutta across a range of regulatory (defined by exploitation rate and size‐based limits) and environmental scenarios (warming vs. concurrent warming and streamflow reduction) in a Mediterranean system. We ran 1, 620 combinations of fishing and environmental scenarios and analysed results using artificial neural networks. In our simulations, (a) climate change and size‐selective fishing both led to a reduced, truncated population, with increased juvenile but decreased adult growth and earlier maturation at smaller size, but fisheries‐induced changes were stronger than those produced by climate change; (b) their effects were additive or dampened but rarely synergistic and (c) phenotypic changes in fitness‐related traits resulted from both evolutionary and plastic processes. Synthesis and applications . Our model‐based analyses highlight that any size‐selective fishing regime would lead to the overexploitation of cold‐water freshwater fish populations if climate warming is accompanied by streamflow reduction—as projected in Mediterranean fisheries. Even if we assumed no future streamflow regime changes, only a limited range of size‐based harvest regulations may provide an acceptable balance between conservation and fishery objectives. Thus, recreational fisheries of cold‐water fish in Mediterranean climates might be more sustainably managed under climate change if conservation‐oriented strategies based on harvest bans (e.g. catch‐and‐release fishing) were implemented. Abstract : Our model‐based analyses highlight that any size‐selective fishing regime would lead to the overexploitation of cold‐water freshwater fish populations if climate warming is accompanied by streamflow reduction—as projected in Mediterranean fisheries. Even if we assumed no future streamflow regime changes, only a limited range of size‐based harvest regulations may provide an acceptable balance between conservation and fishery objectives. Thus, recreational fisheries of cold‐water fish in Mediterranean climates might be more sustainably managed under climate change if conservation‐oriented strategies based on harvest bans (e.g. catch‐and‐release fishing) were implemented. Resumen: Las especies están experimentando cambios evolutivos y/o plásticos en sus rasgos biológicos como respuesta al cambio climático. Sin embargo, la explotación selectiva induce en las poblaciones explotadas cambios fenotípicos en muchos de los mismos rasgos afectados por el cambio climático, pudiendo impedir la adaptación y aclimatación local de los individuos. Analizamos (1) si los cambios fenotípicos inducidos por la pesca recreativa tendrán una dirección y magnitud diferente a los cambios inducidos por el cambio climático, y (2) qué regulaciones pesqueras pueden conducir a la sobreexplotación de las poblaciones bajo las nuevas condiciones ambientales. Utilizando un modelo poblacional eco‐genético basado en individuos simulamos los efectos de la pesca selectiva por tallas sobre una población de una especie sensible a la temperatura (Trucha Común Salmo trutta ) bajo diferentes escenarios regulatorios (definidos por la tasa de explotación y los límites de tallas) y ambientales (aumento en la temperatura vs. aumento en la temperatura simultáneo con reducción en el caudal circulante). Nuestras simulaciones muestran que: (1) el cambio climático y la pesca selectiva por tallas producirían el truncamiento y la reducción de la población, un crecimiento mayor en los juveniles pero menor en los adultos y una maduración más temprana a un tamaño menor; (2) los cambios inducidos por la pesca serían más fuertes que los producidos por el cambio climático y sus efectos serían aditivos o atenuados pero raramente sinérgicos; (3) los cambios fenotípicos producidos resultarían de procesos tanto evolutivos como de plasticidad fenotípica. Síntesis y aplicaciones . Nuestras simulaciones indican que cualquier régimen de pesca selectiva por tallas llevaría a la sobreexplotación de las poblaciones de peces sensibles a la temperatura si el calentamiento climático va acompañado de una reducción del caudal de los ríos, como se prevé en los sistemas mediterráneos. Incluso si no cambiase el régimen de caudales, solo un número limitado de regulaciones por límite de tallas podría proporcionar un balance aceptable entre los objetivos de conservación y de explotación. Por tanto, la pesca recreativa solo sería sostenible si se aplicaran estrategias orientadas a la conservación basadas en regulaciones no extractivas ( e.g . por captura y suelta).